Modeling and Simulation of Sky Survey - Kun Hu; Hongfei Wang; Wenzhao Zhang; Yuohua Xu; Shengmao He (Applied Sciences, 2021)
Sky surveys with wide and deep field are the key direction of international astronomy research for the next decades. It is worthwhile to study how to design a sky survey algorithm to obtain the maximum scientific output in a limited period of observation. In this paper, the modeling and simulation of a wide and deep sky survey mission are presented using a Staged Design Algorithm (SDA), which takes into account the inefficient time periods and difficult-to-observe sky areas. In order to ensure the effective completion of the long-time survey observation tasks in large sky areas, a two-stage scheduling algorithm is designed. Firstly, the inefficient time periods and difficult observation areas are scheduled, and then the overall observation is carried out. The prearranged schedule is arranged when inefficient time periods or difficult areas are encountered during the overall arrangement. The simulation results are verified on the basic data of the China Space Station Telescope (CSST), and the obtained simulation result is three years ahead of the target of the telescope design to complete the wide and deep sky survey of 15,000 deg<semantics>2</semantics>. The design ideas in this paper not only have good results for sky survey observation but also can be extended to similar satellite Earth observation mission planning.